The Agile School Counselor Training Model: Fostering a Nonbinary Professional Identity - Laurie A Carlson; Lorraine DeKruyf; Diana Gruman (Teaching and Supervision in Counseling, 2024)
The authors offer the Agile School Counselor Training Model as a multidimensional framework that provides counselor educators and school counselors-in-training (SCITs) a visual schema for fostering a non-binary professional school counselor identity. The model covers the full spectrum of work school counselors engage in, ranging from mental health professional to educational professional, as well as a continuum of practice that ranges from a focus on the personal to a focus on the systemic. This article reviews the pendulum swings of school counselor professional identity, introduces the Agile Model, and offers implications for practice for counselor educators and SCITs.
Keywords: school counselor; professional identity; agile school counselor training model